2017
DOI: 10.1007/s00261-017-1102-y
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic correlation of transperineal in-bore 3-Tesla magnetic resonance imaging-guided prostate biopsy samples with radical prostatectomy specimen

Abstract: Purpose To determine the accuracy of in-bore transperineal 3-Tesla (T) magnetic resonance (MR) imaging-guided prostate biopsies for predicting final Gleason grades in patients who subsequently underwent radical prostatectomy (RP). Methods A retrospective review of men who underwent transperineal MR imaging-guided prostate biopsy (tpMRGB) with subsequent radical prostatectomy within 1 year was conducted from 2010–2015. All patients underwent a baseline 3-T multiparametric MRI (mpMRI) with endorectal coil and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…Five patients were upstaged to higher-risk groups, indicating more involved definitive therapy. Even with the application of modern imaging and the novel DynaCAD system for MRI-fusion biopsies, our concordance results are consistent with previously published reports ( 13 15 ) and suggest the need for sincere equipoise in delivering partial prostate therapy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Five patients were upstaged to higher-risk groups, indicating more involved definitive therapy. Even with the application of modern imaging and the novel DynaCAD system for MRI-fusion biopsies, our concordance results are consistent with previously published reports ( 13 15 ) and suggest the need for sincere equipoise in delivering partial prostate therapy.…”
Section: Discussionsupporting
confidence: 92%
“…A major limitation of mpMRI-directed partial gland therapy is the variable concordance between imaging and histopathology (13)(14)(15). Rates in the literature range from 12.1% to 69.7% when assessing the accuracy of mpMRI based on confirmatory biopsies and vary depending on Prostate Imaging Reporting and Data System (PIRADS) risk (4,5,13,16).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning surgery outcomes, Velez et al reported their histological results on patients who had radical prostatectomy after fusion biopsy (29). Gleason scores were unchanged in 71% of cases with a Spearman correlation coefficient of 0.75, which is comparable to our study results.…”
Section: Discussionsupporting
confidence: 90%
“…Magnetic resonance imaging (MRI) in prostate cancer allows the opportunity for disease staging and targeted biopsy. [20][21][22] Prostate biopsies performed with the aid of fusion-guided MRI/ultrasonography (US), detected 14.3% of prostate cancers that could not be detected using standard 12-core prostate biopsy. Diagnosis by using fusion biopsy, 86.7% of patients had clinically significant prostate cancer.…”
Section: Discussionmentioning
confidence: 99%